A comparative clinical study of the failure rate of orthodontic brackets bonded with two adhesive systems: conventional and self-etching primer (SEP) - Gladys Cristina Dominguez; André Tortamano; Luiz Vicente de Moura Lopes; Priscilla Campanatti Chibebe Catharino; Camillo Morea (Dental Press Editora, 2013)
OBJECTIVE: This study compared the clinical performance of orthodontic brackets bonded with Transbond adhesive paste after two priming systems: a two-stage conventional system (acid etching + Transbond XT adhesive primer) and a singlestage self-etching primer (SEP) (Transbond Plus). METHODS: The sample comprised 480 metal brackets bonded to the teeth of 24 consecutive patients treated for 36 to 48 months. A split-mouth design was used for bonding, and both systems were used in each patient. Bracket failure rates for each system were analyzed; and failure causes as reported by the patients and the quadrant of teeth for which brackets failed were recorded. RESULTS: The conventional system group had a failure rate of 5.41%, whereas the rate for SEP was 4.58%. In this group, there were 5 failures (38.4%) in the right maxillary quadrant, 2 (15.4%) in the left maxillary quadrant, 4 (30.8%) in the right mandibular quadrant, and 2 (15.4%) in the left mandibular quadrant. In the SEP group, there were 4 (36.4%) failures in the right maxillary quadrant, 1 (9%) in the left maxillary quadrant, 3 (27.3%) in the right mandibular quadrant, and 3 (27.3%) in the left mandibular quadrant. Results of descriptive statistical analysis and odds ratio did not show any significant differences between rates (p = 0.67). CONCLUSION: The clinical efficiency of SEP was similar to that of the conventional system.